Integrative analyses identify HIF-1α as a potential protective role with immune cell infiltration in adamantinomatous craniopharyngioma - Gao, Qiang; Luo, Jing; Pan, Jingjing; Zhang, Longxiao; Song, Dengpan; Zhang, Mingchu; Xu, Dingkang; Guo, Fuyou (Frontiers in Immunology, 2022)
Craniopharyngiomas (CPs) are histologically benign tumors located in the sellar-suprasellar region. Although the transcriptome development in recent years have deepen our knowledge to the tumorigenesis process of Adamantinomatous Craniopharyngioma (ACP), the peritumoral immune infiltration of tumor is still not well understood. In this study, weighted gene co-expression network analysis (WGCNA) was applied to identify different genes modules based on clinical characteristics and gene expression, and then protein-protein interaction (PPI) network with Cytohubba plug-in were performed to screen pivotal genes. In addition, immune cells infiltration (ICI) analysis was used to evaluate the immune microenvironment of ACP patients. In total, 8568 differential expression genes were identified based on our datasets and two microarray profiles from public database. The functional enrichment analysis revealed that up-regulated genes were mainly enriched in immune-related pathways while down-regulated genes were shown in the hormone and transduction of signaling pathways. The WGCNA investigated the most relevant modules and 1858 hub genes was detected, from which PPI network identified 14 pivotal genes, and the HIF-1α pathway including 4 critical genes may involve in the development of ACP. Moreover, naïve CD4+ and CD8+ T cells were decreased while specific subtypes of T cells were significantly increased in ACP patients according to ICI analysis. Validation by immunofluorescence staining revealed higher expression of HIF-1α in ACP (ACP vs control) and adult-subtype (adult vs children), suggesting a possible state of immune system activation. Notably, children with low HIF-1α scores were related to the hypothalamus involvement and hydrocephalus symptoms. In this study, we successfully identified HIF-1α as a key role in the tumorigenesis and development of ACP through a comprehensive integrated analyses and systematically investigated the potential relationship with immune cells in ACP. The results may provide valuable resources for understanding the underlying mechanisms of ACP and strengthen HIF-1α as a potential immunotherapeutic target in clinical application.